Correlates of suicidal ideation in rural Chinese junior high school left-behind children: A socioecological resilience framework - Zhou, Yu-ming; Mak, Leona; Zhao, Chun-xia; He, Fan; Huang, Xiao-na; Tian, Xiao-bo; Yi-zheng,; Sun, Jing (Frontiers in Psychiatry, 2022)
Introduction: Suicide is one of the top five causes of adolescent mortality around the world. The socioecological resilience framework in explaining the risk factors and protective factors for suicidal ideation in left-behind children (LBC) has not been well explored. The current study aims to compare the prevalence of suicidal ideation in LBC and non-LBC, and explore its correlations with resilience factors among LBC. Methodology: This study was part of an epidemiological survey conducted by UNICEF exploring mental health outcomes in left-behind children. We implemented a cross-sectional study collecting data from 11 provinces and 1 municipal , with 5026 participants (3359 LBC, 1667 controls) in year one junior high school living in impoverished areas of rural China. Data on suicidal ideation, self-harm, resilience factors including health-risk behaviours, psychological wellbeing as it was measured by the Strengths and Difficulties Questionnaire, peer relationship within the school environment, and family support were collected. Results: Overall prevalence of suicidal ideation among LBC was 7.2% which is significantly different from 5.5% reported by NLBC (2 = 4.854, p=0.028). LBC reported a higher prevalence of self-harm (16.4%) than NLBC (13.0%; 2 = 10.232, p=0.001), but there was no difference in the prevalence of suicide plan, suicide attempt or help-seeking. LBC had significantly poorer psychological feeling, and greater emotional and behavioural difficulties peer relationship in the school environment than controls. In the multiple logistic regression, history of self-harm was the greatest predictor for suicidal ideation among LBC (OR = 2.078, 95% CI: 1.394-3.100, p<0.001). Health risk behaviour including previous smoking attempt, poor psychological feeling, and emotional and behaviour difficulties, and poor peer relationship within school environment, were also significant risk factors for suicidal ideation among LBC. Conclusion: The prevalence of suicidal ideation and self-harm was greater among left-behind than non-left-behind children. Our results show resilience factors including previous self-harm, emotional and behavioural problems, smoking, and poor peer relationship are significantly associated with suicidal ideation in left-behind adolescents.